P70 The effect of a proactive clinical review in a cohort of primary care COPD patients, low risk by DOSE score. (December 2018) - Rigge, LA; Astles, C; Lippiett, K; Gillett, K; Thomas, DM; Wilkinson, TMA
Abstract : Introduction: COPD is a leading causes of hospital admission in the UK. 1 The DOSE score (Dyspnoea, airways Obstruction, Smoking status, Exacerbation rate) can stratify the risk of subsequent hospital admission. 2 Resource is often focussed on patients with high symptom burden, presenting repeatedly to medical professionals. We hypothesise that early clinical review in lower risk COPD patients may reduce subsequent symptom burden and health care utilisation. Method: A cohort of 120 patients deemed low risk by DOSE score (<4) were identified by primary care electronic record search. 76 patients were randomised to an intervention of diagnosis confirmation, clinical review and optimisation of treatment by a Respiratory Specialist in their GP practice. 44 patients were randomised to a control group offered standard NHS management. Measurement of COPD symptom burden by COPD Assessment Test (CAT) and quality of life using the EQ-5D were recorded at study baseline and twelve months as were COPD exacerbations and respiratory related hospital admissions. Results: 104 patients were followed to study completion at 12 months of whom 87 had a confirmed COPD diagnosis (intervention arm n=53, control arm n=34). At twelve months, in those with confirmed COPD, CAT score improved in both arms (median change −4.4, interquartile range, 5.8 (range-20.0–8.0) vs control −4.3, 5.9 (−19.0–8.0), p=0.930). The EQ-5D index value showed a significantly greater improvement in the intervention arm (median change 0.071, 0.172 (−0.368–0.502) vs control −0.019, 0.251 (−0.487–0.521), p=0.034). The exacerbation rate was lower in the Intervention arm (median exacerbation rate 1.0, 1.0 (0.0–4.0) vs 1.0 2.0 (0.0–7.0) p=0.022) as was the trend in respiratory related hospital admission (0.0% vs 8.8% participants hospitalised, p=0.056). Conclusions: Pro-active specialist review improved quality of life and reduced exacerbation rate and hospitalisation at 12 months in a COPD cohort low risk by DOSE score. If reproducible, this could have cost saving implications. References: Department of Health, UK. Facts about COPD 2010. Available from http://webarchive.nationalarchives.gov.uk Jones RC, et al . Derivation and validation of a composite index of severity in chronic obstructive pulmonary disease: The DOSE index. Am J Respir Crit Care Med 2009;180 (12):1189.